Valoración del riesgo de pie diabético en personas con diabetes mellitus en el Hospital Albrecht - Azabache Martínez, Cinthia Fiorela (2019)
Quantitative research, descriptive method. It was performed in the Diabetes program at the Albrecht Hospital in Trujillo, collecting the data during the month of December 2018, with the objective of assessing the risk of diabetic foot disease. The sample consisted of 185 patients diagnosed with diabetes mellitus. For data collection was obtained through valid and reliable instruments by experts: evaluation of risk factors for diabetic foot. The information collected through the described instruments will be entered and processed in the statistical program IBM SPSS STATISTICS Version 25. The results will be presented in tables of one and double entry, in numerical and percentage form. The following conclusions were reached: The majority were older adults (68.1%). Female sex prevalent (50.8%). Family history higher incidence diabetes (55.7%). Regarding pain symptoms, the highest incidence was occasionally severe (31.4%). Regarding the neurological status the Achilian reflex the result was abnormal (69.7%). Physical examination with signs (57.8%). Arterial vascular state (91.4%). In the overall diagnosis of the foot, the results were normal foot (62.2%). In the stratification of risks they do not present PDN, not EAP, not deformities (62.7%). In self-care the results were inadequate (90.3%). It is concluded that the patients do not present a high risk for a diabetic foot.